The effects of safety culture on project performance in high risk industries - Isaacs, Zieyaad (Department of Electrical Engineering, 2020)
Projects are undertaken at Koeberg Nuclear Power Station in South Africa to enhance safety and to contribute to the continuity of power supply in the country. These projects are undertaken in an industry that is regarded as a high risk due to the potential consequence of a nuclear accident. Focus is thus placed on safety culture to prevent such accidents from taking place. Since safety is a key performance indicator in these high-risk industries, and projects are undertaken to improve the overall performance of such organizations, the role which safety culture has on project performance would be of interest. This study investigates how safety culture influences project performance and identifies the respective elements that collectively interact in contributing towards successful project outcomes in the context of Koeberg Nuclear Power Station. The study has found that - Safety culture plays a vital role in safety performance which is a recognized performance indicator of projects in high risk industries. Safety culture itself was found to consist of the elements of safety performance, personal values to safety, safety leadership, safety related interpersonal relations, proactivity to safety, commitment to safety and continuous improvements to safety. These elements with emphasis on safety were related to the project management knowledge areas of Time, Scope, Risk, Quality, Human Resource and Communication Management. The project managers competencies are also included amongst these elements which respectively interact with one another to influence the level of safety culture in a project. The study has revealed that these elements should be worked at by all departments involved in a project to allow the required performance criteria to be achieved. In addition, it reveals that a good safety culture provides flexibility in addressing changing requirements in a project.